2012
DOI: 10.1161/strokeaha.111.636449
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor for Mobilizing Bone Marrow Stem Cells in Subacute Stroke

Abstract: Background and Purpose-Granulocyte-colony stimulating factor (G-CSF) is neuroprotective in experimental stroke and mobilizes CD34 ϩ peripheral blood stem cells into the circulation. We assessed the safety of G-CSF in recent stroke in a phase IIb single-center randomized, controlled trial. Methods-G-CSF (10 g/kg) or placebo (ratio 2:1) was given SC for 5 days to 60 patients 3 to 30 days after ischemic or hemorrhagic stroke. The primary outcome was the frequency of serious adverse events. Peripheral blood counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 22 publications
2
46
0
1
Order By: Relevance
“…Previous studies found that G-CSF-mobilized stem cells infiltrate injured tissues to promote neural repair (28,88,104). As mentioned above, G-CSF displayed capacity to cross the BBB to act upon neurons and glial cells through the G-CSF receptor (134), of which their activation has been demonstrated to downregulate expression of proinflammatory cytokines and to enhance neurogenesis (95,115).…”
Section: Combination Therapy Of G-csf and Transplantation Of Umbilicamentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies found that G-CSF-mobilized stem cells infiltrate injured tissues to promote neural repair (28,88,104). As mentioned above, G-CSF displayed capacity to cross the BBB to act upon neurons and glial cells through the G-CSF receptor (134), of which their activation has been demonstrated to downregulate expression of proinflammatory cytokines and to enhance neurogenesis (95,115).…”
Section: Combination Therapy Of G-csf and Transplantation Of Umbilicamentioning
confidence: 91%
“…Currently, a limited clinical trial is under way for testing G-CSF in TBI patients (personal communication with Dr. Juan SanchezRamos, USF/VA). Despite inconsistent efficacy results, the translation of G-CSF for TBI in the clinic is based on the drug's safety profiles for its indication in acute ischemic stroke and AD (28,87,88,103,104).…”
Section: Therapeutic Uses Of G-csfmentioning
confidence: 99%
“…[12][13][14]20,22,24,31,32,65,[66][67][68][69][70][71]74 In addition to dextran, seven other types of SPION coatings were identified, such as starch, phosphatidylcholine, DEAE-diphosphate starch and poly-diallyl-dimethylamine in the Riegler et al 72 study; carboxylated iron oxide core was seen in the Detante et al 64 study, silica in the study by Wang et al 63 monomer citrate in the study by Stroh et al 23 and DPPA in the study by Bjorklund et al 19 There was one study 62 that used both dextran and chitosan.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the analysis of the SPION cell labeling process by the 32 selected articles, the majority (19) used mesenchymal stem cells (MSC), six articles 12,19,23,33,66,74 used embryonic stem cells, five articles 20,25,30,70,76 used neural stem cells, one article 65 used hematopoietic stem cells, and the other article 31 used amniotic fluid-derived stem cells ( Table 2). The use of a transfection agent and a culture medium to optimize the stem cell labeling process with SPION is usual.…”
Section: In Vitro Experiments For Stem Cell Labelingmentioning
confidence: 99%
See 1 more Smart Citation